8 Ways to draw a Fish - Luisa Martelo (Chennai, India Tara Books, 2017)
The fish is imagined and rendered in eight different folk and tribal styles. Through tracing, patterning and colouring the fish, the child can immerse herself in detailed exploration of styles - or just have fun. Older children will begin to understand that art is as much about the imagination as it is about depiction.
Keywords: PY-Art -- PY-Art